Adopting tomorrow’s therapies today: a perspective review of adoptive cell therapy in lung cancer - Faith Abodunrin; Daniel J Olson; Oluwatosin Emehinola; Christine M Bestvina (Therapeutic Advances in Medical Oncology)
Lung cancer is the leading cause of all cancer-related deaths in the United States and remains a global health challenge. While targeted therapy has revolutionized the treatment landscape of nonsmall cell lung cancer, many patients lack actionable mutations. Immunotherapy, particularly immune checkpoint inhibitors (ICIs), have significantly impacted outcomes in lung cancer in the last decade. Some patients, however, never respond or become refractory to ICIs. Newer therapies aimed at augmenting the immune system and enhancing antitumor effects are currently being explored. Adoptive cell therapy (ACT) employs T cells isolated from either tumors or peripheral blood and often engineers them to effect antitumor immune response. Chimeric antigen receptor T (CAR-T) cell therapy, engineered T cell receptor therapy, and tumor-infiltrating lymphocytes are examples of adoptive cellular therapies. CAR-T cell therapy has been successful in the treatment of hematological malignancies with several CAR products gaining approval in the treatment of refractory blood cancers. The success of ACTs in hematological cancers has fueled research into the role of these therapies in solid cancers including lung cancer. Many trials have had early promising results, with many clinical trials currently enrolling. There are many limitations to the efficacy of ACTs, as well as risks and benefits with the individual subtypes of ACT. With growing knowledge about tumor antigens and more advanced cell engineering, there is potential for ACT to result in durable responses in immunologically “cold” tumors. Here, we review the major subtypes of ACTs, evidence supporting their use in lung cancer, challenges, and future perspectives in ACTs. Additionally, we include T cell engagers and mRNA vaccine studies and potential combinatorial strategies in lung cancer.